Estudo de caso: a Universidade Católica de Brasília. Práticas de ensino nas disciplinas de formação humana nas universidades confessionais - Alves, Vicente Paulo (2003)
The present work studies the case of the human development disciplines lectured at the Universidade Católica de Brasília, aiming at gathering the perception from the students of the subjects Science of Religion and Anthropology of Religion, as well as that of the professors of such subjects. Grounded in six education theorists and in similar researches done in the past, this project will attempt to present pedagogical and methodological strategies for the aforementio ned subjects. Analyzing the documentation from the Institution, we have reached the idea that the learning-teaching process must be based on freedom and dialogue. With the students, two researches were carried out, one in the beginning and one in the end of the term so as to identify the changes which may have occurred in the period. Finally, all professors from both subjects were interviewed about their teaching style, lesson preparation, testing, etc, so the information could be contrasted to the students . The conclusion applied the data found to the confessional universities which also offer such or similar subjects in the pedagogical project as those from the Univesidade Católica de Brasília.(AU)